Perbandingan Analisis Struktur Gedung Laboratorium PGSD Universitas Samudra Metode Sistem Rangka Pemikul Momen Khusus Menggunakan ETABS dan BIM Tekla Struktural Designer - Syah, Muhammad Azis; Ardhyan, Muhammad Zacky; Fajri, Haikal; Purwandito, Meilandy; Irwansyah, Irwansyah (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
Indonesia is located on the fault line of the Eurasian and Indo-Australian plates which makes Indonesia prone to earthquakes. The structural design of the Special Moment Resisting Frame System (SRPMK) is required for reinforced concrete buildings in high earthquake-prone areas, it is hoped that using the SRPMK construction method can have a flexible structure. The purpose of this research is to discuss the comparison of test control of the Samudra University PGSD Laboratory Building with the Etabs application and the Tekla Structural Designer Application. The building structure under review is a reinforced concrete structure with 3 floors with a building length of 54 m, width of 18 m, and height of 16.8 m. The type of soil for the construction site is soft soil with earthquake design category D. Construction planning refers to SNI 1726 – 2019. The additional dead loads of floors and roofs are 0.672 and 0.710, the largest live loads are 7.18 kN/m², the earthquake loads with Ss and S1 are 0.68 and 0.34, the priority factor earthquake of 1.5 and a period of 20 seconds, the suction and compressive wind loads are -0.25 kN/m² and -0.41 kN /m². The results of structural analysis using the ETABS application and the Tekla Structural Designer application, the control values of the mass participation test, the fundamental natural vibration time, the base reaction, and the standard deviation between floors have met the requirements for earthquake-resistant building planning. The volume of concrete is 594.9 m³, the bone requirement for D22 is 3432.96 kg, D19 is 3605 4.89 kg, D16 is 26434.5 kg, D13 is 1774.72 kg, Ø12 is 6237.53 kg, Ø10 is 31599, 07 kg, Ø8 is 4589.31 kg